Sunagocia omanensis, a new flathead fish (Scorpaeniformes, Platycephalidae) from the Western Indian Ocean, with comments on the distribution of Sunagocia carbuncula - Knapp, Leslie W.; Randall, John E. (Zootaxa, 2013)
A new species of Platycephalidae having a weak development of sensory tubules on the cheek is placed in the genus Sunagocia Imamura. The description is based on two specimens taken at the Kuria Muria Ids., Oman. The new species may be distinguished from its congeners by having three preocular spines, ethmoid spines forming a rosette on mid-line with 5–6 tips coming from a common base, and a body coloration of tan with dark saddles reaching to lower sides. It is also characterized by having numerous small serrations along the supraorbital and suborbital ridges and sixgill rakers. A section concerning the status and range of Sunagocia carbuncula Valenciennes in the western Indian Ocean is also included . A key separating the species of Sunagocia appears below.